THE EFFECTIVENESS OF DRAMA TO TEACH SPEAKING VIEWED FROM STUDENTS’ SELF-ACTUALIZATION - Wiyanti, Senny; Asib, Abdul; Ngadiso, Ngadiso (Jurnal Pendidikan Bahasa, 2018)
The main objective of the research is to find out: (1) whether Drama technique is more effective than Guided Conversation Activity Technique to teach Speaking; (2) whether the students who have high self-actualization have better speaking skill than those who have low self-actualization; and (3) whether there is an interaction between teaching techniques and students’ self-actualization. The method of this research was quantitative research using an experimental design. The research findings are: (1) Drama Technique is significantly different from Guided Conversation Activity (GCA) technique to teach speaking because Fo is higher than Ft. (2) the speaking skill of the students who have high self-actualization is significantly different from that of those who have low self-actualization if viewed from the result of ANOVA because Fo is higher than Ft. (3) there is an interaction between teaching techniques and self-actualization for teaching speaking because Fo is higher than Ft.Keywords: drama, self-actualization, guided conversation, speaking.